2004
DOI: 10.1073/pnas.0400354101
|View full text |Cite
|
Sign up to set email alerts
|

The herpes simplex virus 1 U L 41 gene-dependent destabilization of cellular RNAs is selective and may be sequence-specific

Abstract: In cells infected with herpes simplex virus 1, the RNA encoded by the stress-inducible immediate early response gene IEX-1 was up-regulated immediately after infection. However, the accumulated RNA was degraded 3 -5 , and the protein was detectable only at very early times after infection. The degradation was dependent on the U L41 gene encoding the virion host shutoff (vhs) protein and resulted in the accumulation of truncated RNA containing the 5 -end portion of the transcript. IEX-1 contains an AU-rich elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
122
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(139 citation statements)
references
References 26 publications
11
122
6
Order By: Relevance
“…The results described above were in agreement with the pattern of degradation of IEX-1 mRNA observed in HSV-1-infected cells and specifically with the lingering of truncated 5Ј domains, generated by vhs-dependent endonucleolytic cleavage within the AREs (19,21). The objective of the experiments described in this section was to test whether a substrate, consisting of only IEX-1 coding sequence domain (CDS, substrate 3), was cleaved by the purified GST-vhs fusion protein.…”
Section: The Locations Of Vhs Cleavage Sites In Truncated Transcriptssupporting
confidence: 78%
See 2 more Smart Citations
“…The results described above were in agreement with the pattern of degradation of IEX-1 mRNA observed in HSV-1-infected cells and specifically with the lingering of truncated 5Ј domains, generated by vhs-dependent endonucleolytic cleavage within the AREs (19,21). The objective of the experiments described in this section was to test whether a substrate, consisting of only IEX-1 coding sequence domain (CDS, substrate 3), was cleaved by the purified GST-vhs fusion protein.…”
Section: The Locations Of Vhs Cleavage Sites In Truncated Transcriptssupporting
confidence: 78%
“…Although we do not contest the conclusion that the vhsdependent degradation of some mRNAs initiates at or near the 5Ј terminus, studies carried out in our laboratory do not support the concept that vhs mediates indiscriminate degradation of mRNAs or that the degradation invariably proceeds 5Ј to 3Ј (19). Examination of the relative rates of degradation of several cellular mRNAs upon HSV-1 infection led to the conclusion that cellular RNAs form at least three classes based on their fate after infection.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In BoHV-1 infected cells, the cellular protein synthesis is shut off in part by the vhs tegument protein [76,95]. By analogy to the HSV-1 UL41 encoded protein, the latter is supposed to degrade mRNA preexisting in the target cell [48,99]. Several studies were devoted to the regulation of apoptosis during productive BoHV-1 infection.…”
Section: Replication At the Mucosal Portal Of Entrymentioning
confidence: 99%
“…So far, several virus gene products, for example HSV UL41 (Esclatine et al, 2004) and KSHV KaposinB (McCormick and Ganem, 2001), have been shown to have the potential to control the fate of ARE-mRNA. In the late phase of adenovirus infection, although the export of the bulk of cellular mRNA is inhibited, ARE-mRNA is exported into the cytoplasm (Higashino et al, 2005).…”
Section: Discussionmentioning
confidence: 99%